Digital Storytelling Berbasis Refleksi Kritis dalam Pembelajaran Bahasa Indonesia: Menumbuhkan Kesadaran Multikultural dan Keterampilan Tekno-Pedagogis Calon Guru" - Yuliarti; Norhayati (Advances In Education Journal, 2026)
This study aims to investigate the implementation of critical reflection-based Digital Storytelling (DST) in Indonesian language learning to foster multicultural awareness and techno-pedagogical skills in student teachers. The study used a qualitative approach This study involved 35 pre-service teachers enrolled in the Primary Islamic Teacher Education (PGMI) Program at Universitas Islam Negeri Palangka Raya, Indonesia. Data were collected through digital portfolios, semi-structured interviews, classroom observations, and student reflective journals. Data analysis was conducted using the thematic analysis model of Braun and Clarke. The results of the study indicate two main themes, namely the reconstruction of multicultural awareness through the deconstruction of cultural bias and the escalation of techno-pedagogical skills through the use of multimodal media and artificial intelligence-based technology. The findings indicate that critical reflection-based DST can encourage the transformation of student perspectives, increase intercultural empathy, reduce social stereotypes, and strengthen digital instructional design skills. This study contributes to the development of a transformational learning model that integrates Transformative Learning , Multicultural Education , TPACK, and AI Literacy in student teacher education.